Methodological Aspects of Development of Gels for Treating Inflammatory Dental Diseases - Khokhlenkova, Natalia V. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Inflammatory periodontal diseases take one of the first places among dental diseases; they are prevalent in various age groups and tend to grow steadily. The highest morbidity rate is found at the age from 15 to 44, that is 64-98% of the population. For the rational pathogenetic therapy, multiagent medications affecting different parts of the pathological process in a multiple way should be developed. Materials and Methods: In the work, marketing and economic research methods are used to ground social and medical practicability of developing new dental products for local treatment. Results and Discussions: With reference to the analysis of the Ukrainian market, it was found out that a dominant position in the range of dental gels, presented at the national pharmaceutical market is held by imported preparations. Methodological approaches to developing semisolid dosage form for treating inflammatory periodontal and oral mucosa diseases were summarized. Conclusions: Methodological approaches to developing medicine in gel dosage form for treating inflammatory periodontal and oral mucosa diseases were developed. With reference to the proposed methodology for developing gel for applying in dental practice, we theoretically and experimentally grounded the structure and rational technology of new combination preparations â€œAloe-Dentalâ€ and â€œDentatriginâ€ in the form of gels.